Synthesis and Enhanced Properties of Fluorescence-Based Polyurethane Films by Covalently Bonding 1,8-Naphthalimide - Ma, Y.; Tang, Q.Y.; Wang, L.H.; Yao, C. (Asian Journal of Chemistry, 2014)
A series of fluorescence-based polyurethane films (AABD-PUs) were synthesized by covalently bonding different amounts of 2-(2-aminoethyl)-6-((2-aminoethyl)amino)-1H-benzo[de]isoquinoline-1,3(2H)-dione (AABD) into polyurethane chains as a chain extender, which was a novel amino-functionalized 1,8-naphthalimide fluorescent dye. The chemical structure of AABD was confirmed by 1H NMR and FT-IR spectra. The AABD segments content in synthesized AABD-PUs was investigated by ultraviolet visible spectroscopy (UV-visible) and the enhanced properties of AABD-PUs were characterized by fluorescent spectroscopy. It was found that the UV-visible absorption and the fluorescence emission maximum of AABD-PUs showed blue shift in comparison with those of AABD, respectively. The fluorescence intensity of AABD-PUs was observably enhanced due to the changes of micro-circumstance of AABD. Furthermore, the fluorescence of AABD-PUs showed quite good stability, not only for the temperature but also for the fluorescence quencher. Additionally, the fluorophore was fixed permanently into polyurethane chains and was difficult to migrate.